A theoretical review of contract cheating in master's and doctoral studies: Some global trends and perspectives - Mtshweni, B. (South African Journal of Higher Education, 2024)
The surge of contract cheating cases among postgraduate students enrolled for master’s and doctoral studies is a serious challenge to the academic integrity of higher education qualifications globally. Evidence suggests that there is a dearth of studies on contract cheating at master’s and doctoral levels of study. Most studies on contract cheating have focused primarily on undergraduate students. This article uses a theoretical review as a method of inquiry to examine the phenomenon of contract cheating among postgraduate students enrolled for master’s and doctoral studies. The article explores the practice of contract cheating among postgraduate students from a global perspective while making reference to research conducted in African institutions of higher learning. Further, the article uses the neutralisation theory to unravel the underlying factors that contribute to contract cheating in postgraduate studies. The ramifications of contract cheating for students and higher education institutions are interrogated. Additionally, the article provides a discussion on intervention strategies that institutions of higher learning could consider, using a multi-sectoral approach to curb contract cheating, promote and instil ethical scholarship in master’s and doctoral studies.